The application of digitization and digital marketing for the recovery of Ukraine’s economy - Nazarenko, N.; Nochovka, A. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2024)
The article explores the potential application of digital technologies and digital marketing for the post-war recovery of Ukraine’s economy. The war in Ukraine has led to significant destruction and economic losses, making it crucial to explore pathways for recovery and development of the Ukrainian economy using modern digital tools. It is noted that the analysis and justification of the role of digital technologies in economic recovery from the perspective of digital marketing have not been adequately explored. The purpose of the article is to analyze the characteristics of digitalization and digital marketing and to determine the possibilities of their further application for the development and post-war recovery of Ukraine’s economy. The main direction of state development in the field of digital technologies has been identified. The article investigates the emergence of the term "digital marketing" and provides an author’s definition of the concept. An overview of the fundamental theoretical provisions of this category is presented. The basic principles of implementing and operating digital marketing in conditions of armed conflict are clarified. The main advantages and challenges of applying digital marketing for economic recovery are analyzed. The rapid adaptation of digital marketing to changes and a focus on continuous improvement of knowledge regarding new methods and tools in this field are examined. The article contains recommendations for the implementation of digitalization and digital marketing in various sectors. For successful application of digital marketing methods and tools, the government, businesses, and civil society must adopt a comprehensive approach. The practical application involves applying the findings of the study to further develop strategies for post-war recovery of the state. Recommendations for the implementation of digitalization and digital marketing can be beneficial for enterprises, government bodies, and civil organizations.